Pertumbuhan dan Perkembangan Jiwa Beragama Anak Usia 6-8 Tahun - Lubis, Ramadhan; Khoirunnisa, Ardina; Siagian, Amalia Alfina; Kesuma, Bunga; Pratiwi, Eyzi; Rangkuti, Khairina Habib; Simanjuntak, Miftah Hayatih (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Growth is the process of increasing quantity or size. Development is the process of changing the function or working capacity of the body's organs into a state that is increasingly organized (controlled) and specialized (in accordance with the wishes of each function). The influence of emotional-cognitive development is caused by the psychomotor abilities of children aged 6 to 8 years. In this case, we can communicate that development includes cognitive, emotional and psychomotor abilities. In this research, the method used is qualitative research methods. The qualitative method in question is one of the studies carried out using Observation and Interview methods. The results of the research show that the influence of emotional-cognitive development is caused by the psychomotor abilities of children aged 6 to 8 years. This can be seen when a child is still small when he is asked to to the mosque to pray and he wants to. When he prays this prayer, he knows how to pray because his parents told him to do it also when psychomotor effects on children occur when they perform their prayers without parents or influence. The influence on them is an emotional thing that happens to them. This is caused by development and growth occurring in children, usually there are factors, because parents are used to it. When he sees his parents praying, he usually prays too. For example, parents set a good example, then they follow the good example and it can be said that parents have a big influence on children's growth and development.